Uprawa winorośli na średniowiecznym Śląsku- stan badań, źródła i metody - Adamska, Dagmara (Stowarzyszenie Historyków Sztuki, 2021)
Most of the information on the numerous but small Silesian vineyards is contained in documents; the data tend to be perfunctory and scattered. Accounts from narrative sources and toponomastics offer complementary information. On the basis of an analysis of local names and documentation, it can be concluded that the oldest cultivation in Silesia dates back to the end of the 12th century and can be linked to the activities of Bolesław Wysoki and Henryk Brodaty and monastic activity. Most information is found in sources from the 14th century. City seals with wine motifs also date from that time. References from the 15th and 16th centuries are less frequent, and the memory of the region’s wine-making traditions faded in the centuries that followed. As a result, the use of the retrospective method of modern cartography tends to be unreliable, since 18th century microtoponyms can only sporadically be linked to the functioning of medieval vineyards.